Social Security Incentives and Human Capital Investment - Morten I. Lau; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2001)
While the effect of social security systems on retirement decisions has received much attention, the impact of these systems on individuals' incentives to invest in their human capital has not been analyzed. We integrate human capital investment and retirement decisions in a simple analytical life-cycle model with full certainty and investigate how different social security schemes may aect welfare, human capital investment and labor supply. We analyze and compare three different social security systems. Our results suggest that actuarial adjustment and the link between individual social security contributions and benefits increase human capital investment and postpone retirement.
Keywords: 330; Social security; retirement; education; human capital; labor supply